PBI-Blended Membrane Evaluated in High Temperature SO2 Electrolyzer. (10th April 2018) - Peach, Retha; Krieg, Henning; Kruger, Andries; Bessarabov, Dmitri; Kerres, Jochen A.
Abstract : It has been shown that hydrogen can be produced efficiently within the membrane based Hybrid Sulfur (HyS) process, where SO2 is electrochemically oxidized in the presence of H2 O to produce H2 and H2 SO4 . In earlier studies, it was shown that PBI-type membranes were able to maintain high conductivities at lower potentials in highly acidic environments while having excellent thermal stabilities. Lately, more hydrogen producing technologies have focused on higher operation temperatures (>100 °C) for improved efficiencies while keeping cost competitiveness. Within this study we characterized a novel cross-linked partially fluorinated poly-aromatic PBI-blended membrane within the SO2 electrolyzer at 120 °C in comparison to earlier work at 80 °C. Lower cell voltages were achieved for current densities up to 1.1 A/cm 2 . Stable operating voltage at 0.3 A/cm 2 was achieved with minimal degradation which proves promising for future developments.